Multichannel Fenestrations of the Petrous Segment of the Internal Carotid Artery - Mangla, Sundeep; Teitelbaum, George P. (American Journal of Neuroradiology, 1999)
Summary: Multichannel fenestration of the internal carotid artery (ICA) is a rare, previously unreported developmental anomaly with unknown clinical significance. Although previously thought to have distinct embryologic origins, the presence of multiple channels in a short-segment fenestration favors a common developmental pathway for the origin of duplications and fenestrations: the persistence of a plexiform vascular network from the 4-mm to 5-mm embryologic stage of development.